OPTN/SRTR 2013 Annual Data Report: Kidney. Issue 2 (January 2015) - Matas, A. J.; Smith, J. M.; Skeans, M. A.; Thompson, B.; Gustafson, S. K.; Stewart, D. E.; Cherikh, W. S.; Wainright, J. L.; Boyle, G.; Snyder, J. J.; Israni, A. K.; Kasiske, B. L.
ABSTRACT A new kidney allocation system, expected to be implemented in late 2014, will characterize donors on a percent scale (0%‐100%) using the kidney donor profile index (KDPI). The 20% of deceased donor kidneys with the greatest expected posttransplant longevity will be allocated first to the 20% of candidates with the best expected posttransplant survival; kidneys that are not accepted will then be offered to remaining 80% of candidates. Waiting time will start at the time of maintenance dialysis initiation (even if before listing) or at the time of listing with an estimated glomerular filtration rate of 20 mL/min/1.73 m2 or less. Under the current system, the number of candidates on the waiting list continues to increase, as each year more candidates are added than are removed. Median waiting times for adults increased from 3 years in 2003 to more than 4.5 years in 2009. Donation rates have not increased. Short‐term outcomes continue to improve; death‐censored graft survival at 90 days posttransplant was 97% or higher for deceased donor transplants and over 99% for living donor transplants. In 2013, 883 pediatric candidates were added to the waiting list; 65.8% of pediatric candidates on the list in 2013 underwent deceased donor transplant. Five‐year graft survival was highest for living donor recipients aged younger than 11 years (89%) and lowest for deceased donor recipients aged 11 to 17 years (68%).